Dental caries as a common dental disease: prevalence and association with gastrointestinal pathology in children (a literature review) - M. O. Lysak (Zaporožskij Medicinskij Žurnal, 2025)
Dental caries is the most widespread dental disease, with a prevalence among the pediatric population worldwide ranging from 39.6 % to 75.43 %, and an intensity of 0.89–3.40 teeth. In Ukraine, the prevalence of dental caries varies from 42 % to 96 %, with an intensity of carious lesions ranging from 0.07 to 6.50 teeth. Higher rates of dental caries have been observed in children with somatic diseases, which contribute to the formation of deficient dental hard tissue structure, reduced enamel resistance, and favorable conditions for caries development.